Consumers’ Opinions on the Plastic Bag Ban and Using Eco-Friendly Bags for Shopping in Pakistan - Maryam Zaheer; Basharat Hussain; Tehniyat Fatima; Alison Edgley (Asian Journal for Public Opinion Research)
To address threats to the natural environment, the government in Pakistan has banned use of plastic bags for shopping. The concept of governmentality presented by Michel Foucault explores the techniques of governance and defines law not just as the manifestation of sovereign power but also as a technique of governance involving a range of organized practices designed to shape mentalities to achieve certain desired ends in subjects which claim to be for the welfare of the population. The present study explores the perceptions of the consumers regarding the rationality of the government behind the ban and also highlights the effectiveness of the use of law as a technique of governance. A qualitative approach was used by conducting fifteen interviews with young consumers selected through convenience sampling. The findings suggest that the rationality of the government behind the ban was received well by the consumers and the ban was viewed as a positive and pro-environmental step. The use of law as a technique of governance also proved to be effective in the said case because the people did not perceive the law as coercive despite the radical change it brought to their shopping practices. The present study contributes to the development of the theoretical understanding of governmentality and its sub-concept of the use of law as a technique of governance.